(untitled) (Marketing Journal, 2025)
This article examines the issues of effective formation of marketing strategies of insurance companies in the context of modern digital technologies. In the context of digital transformation, modern methods of selling insurance services and developing relationships with customers have been analyzed. As a result of the study, recommendations for the integrated use of digital marketing tools have been developed.